2009
DOI: 10.26719/2009.15.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Stunting among primary-school children: a sample from Baghdad, Iraq

Abstract: The aim of this study was to establish baseline information about the prevalence and distribution of growth deficit (stunting) in a sample of Iraqi schoolchildren from the capital, Baghdad. A cross-sectional descriptive analysis of the growth status of 5286 primary-school children aged 7-12 years (2888 males, 2398 females) was conducted by measuring the prevalence of stunting (height-forage Z-score < -2), and underweight (body mass index-for-age) using the NCHS/WHO and IOTF/WHO cutoff values respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
2
19
1
1
Order By: Relevance
“…However, comparing the current findings with surveys conducted among noninstitutionalized school age children, similar prevalence of stunting was reported from Ethiopia (14.3%) and Palestine (14.4%) [45, 46], while a slightly higher prevalence was seen in Nigeria (17.4%) and Iraq (18.7%) [47, 48]. Furthermore, a large study conducted among rural schoolchildren in low-income countries (Ghana, Tanzania, Indonesia, Vietnam, and India) found the overall prevalence of stunting and underweight to be high in all 5 countries, ranging from 48 to 56% [49].…”
Section: Discussionsupporting
confidence: 82%
“…However, comparing the current findings with surveys conducted among noninstitutionalized school age children, similar prevalence of stunting was reported from Ethiopia (14.3%) and Palestine (14.4%) [45, 46], while a slightly higher prevalence was seen in Nigeria (17.4%) and Iraq (18.7%) [47, 48]. Furthermore, a large study conducted among rural schoolchildren in low-income countries (Ghana, Tanzania, Indonesia, Vietnam, and India) found the overall prevalence of stunting and underweight to be high in all 5 countries, ranging from 48 to 56% [49].…”
Section: Discussionsupporting
confidence: 82%
“…In the age group 13-15 years old, boys were more stunted than girls. The others study in Nigeria Abeokuta indicated the prevalence of stunting was higher among young female children 5-9 years of age while as the age increased boys were more stunted [15]. This could be attributed to socio cultural influence; at the early age parents give priority care for boys than girls.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, the prevalence of stunting among school children was found to be high, which was 48.1%. This was the highest as compared studies, in Nigeria 17.4% [14], in Kenya 16.64 % [11], in Baghdad Iraq 18.7% [15] and in India 18.5 % [16]. This may be attributed due to differences in socio-economic, cultural, educational, feeding habits, genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies from developing countries reported similar prevalence data for stunting: 6.2%-15.2% in schools in Brazil in 1990 (19), 15 (25), and 16.5% in rural areas of southern Pakistan in 2005 (26). The prevalence of stunting only, and concurrent stunting and underweight, in Baghdad, Iraq 2009 were 18.7% and 13.5% respectively (27). Chronic undernutrition, as evidenced by the proportion of stunted children, was of mild prevalence in this school-aged cohort (18.7%) and the overall prevalence of linear growth deficit was 53.3%.…”
Section: Discussion:-body Composition and Anthropometric Measurements:-mentioning
confidence: 72%